Commercial Diplomacy of PT INKA (PERSERO) Indonesia in the Export of Goods Carriage for KiwiRail New Zealand in 2021 - Mohamad Latief; Yulia Rimapradesi; Farhan Riswandha Jhuswanto (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
This article explains the PT INKA role in freight cars export for KiwiRail New Zealand. The concepts used are commercial diplomacy, nation branding, and ta'awun. This research uses a qualitative approach with literature study toward books, journals, and online and offline media. This study found that PT INKA carried out commercial diplomacy in the form of export activities, business collaborations, and trade promotions which made PT INKA known in the global market. This make UGL Rail to enter into a contract with PT INKA. Furthermore, UGL Rail contacted PT INKA to ask for its willingness to fulfill the KiwiRail supply tender. Thus, PT INKA Indonesia's commercial diplomacy does not only as a supplier that helps UGL Rail to fulfill contracts for the procurement of container flat top wagons for KiwiRail New Zealand, but also as a promotion for the company and also Indonesia as their country of origin internationally.